Request strategies in Norwegian and English - Awedyk, Witosław (Folia Scandinavica Posnaniensia, 2007)
This paper discusses verbal reahzation of one reąuest situation which has been used in the empirical part of my doctoral dissertation (Awedyk, 2001) which sets out to compare and contrast reąuest strategies in the reahzation of the speech act of reąuest in Norwegian and English. Due to the limitations of space, I will only be able to present a smali fraction of the findings resulting from the project I carried out. Notwithstanding the above, some of the problems discussed below can be perceived as representative of the generał pragmalinguistic phenomena present in the respective languages.